Infeksi Ascariasis Dan Anemia Pada Anak Stunting di Desa Bone, Kabupaten Kupang, Nusa Tenggara Timur - Meliance Bria; Ni Made Susilawati (Jurnal Ventilator, 2023)
. Helminth infection is one of the health problems in all tropical countries in the world including Indonesia. Ascaris lumbricoides is one of the Soil Transmitted Helminths (STH). Stunting are the age group that is vulnerable to helminth infection including ascariasis. A. lumbricoides infection can cause serious effects if not treated and without a clean and healthy lifestyle. Therefore, it is necessary to conduct research on the prevalence of A. lumbricoides infection and hemoglobin (Hb) level in its infected hosts. The design of this study was observational analytic with cross sectional study. The subjects of the stunting in Bone Village. The sample technique used in this method is the total population. Diagnosis was performed microscopically by Kato-Katz method and Hb levels were measured using a hematology analyzer. Microscopy examination found 6.4% eggs of A. lumbricoides and a low hemoglobin level of 22,5%, students infected with A. lumbricoides in Bone Village with very low hygiene and sanitation.